2020
DOI: 10.3201/eid2601.190159
|View full text |Cite
|
Sign up to set email alerts
|

Elephant Endotheliotropic Herpesvirus Hemorrhagic Disease in Asian Elephant Calves in Logging Camps, Myanmar

Abstract: In recent years, an alarming number of cases of lethal acute hemorrhagic disease have occurred in Asian elephant calves raised in logging camps in Myanmar. To determine whether these deaths were associated with infection by elephant endotheliotropic herpesvirus (EEHV), we conducted diagnostic PCR subtype DNA sequencing analysis on necropsy tissue samples collected from 3 locations. We found that EEHV DNA from 7 PCR loci was present at high levels in all 3 calves and was the same EEHV1A virus type that has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Over the last decades, nearly 20% of all Asian elephant calves born in Western zoos succumbed to EEHV-HD [ 1 ]. Furthermore, multiple reports showed that the disease affects both captive and wild elephants in the Asian elephant range countries [ 4 , 5 , 6 ]. How widespread the virus is, and its prevalence in free-living populations, has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, nearly 20% of all Asian elephant calves born in Western zoos succumbed to EEHV-HD [ 1 ]. Furthermore, multiple reports showed that the disease affects both captive and wild elephants in the Asian elephant range countries [ 4 , 5 , 6 ]. How widespread the virus is, and its prevalence in free-living populations, has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, both the assessment of EEHV infections of individual animals and the assessment of herd prevalence are largely performed using PCR on blood samples [ 5 , 6 , 9 ]. Latent EEHV infections can only be detected upon reactivation, hence detection of EEHV prevalence by PCR requires longitudinal sampling over an extended period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Several health problems affect elephants both in situ and ex situ that could benefit from a better understanding of underlying disease processes and improved tools for detection and monitoring. Elephant endotheliotropic herpesvirus hemorrhagic disease (EEHV HD) affects almost one in four Asian elephant calves born in zoos globally [ 28 ], as well as African elephants [ 17 , 29 , 30 ], and in captive and wild populations in Asia [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. One proposed hypothesis for the severity of EEHV HD could be that immunologically naĂŻve calves fail to mount an effective immune response to keep up with viral replication [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, nearly 20% of all Asian elephant calves born in Western zoos succumbed to EEHV-HD (1). Furthermore, multiple reports showed that the disease affects both captive and wild elephants in the Asian elephant range countries (4-6). How widespread the virus is, and its prevalence in free-living populations, has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, both the assessment of EEHV infections of individuals animals and the assessment of herd prevalence are largely performed using PCR on blood samples (5, 6, 9). Latent EEHV infections can only be detected upon reactivation, hence detection of EEHV prevalence by PCR requires longitudinal sampling over an extended period of time.…”
Section: Introductionmentioning
confidence: 99%